The Role of Tuan Syekh H. Muhammad Bahri Nur Nasution in the Founding Team of IAIN North Sumatra in 1973 - Tanjung, Sri Ramadini; Nasution, Kasron; A, Achiriah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the role of Tuan Syekh H. Muhammad Bahri Nur Nasution in the founding of the State Institute for Islamic Studies (IAIN) of North Sumatra and his contributions to religious, social, and educational fields. This research employs a qualitative method with a historical approach. Data were collected through interviews, observation, and document analysis, while data analysis was conducted through the stages of heuristics, source criticism, interpretation, and historiography. The findings indicate that Tuan Syekh H. Muhammad Bahri Nur Nasution was a charismatic Islamic scholar who possessed strong scholarly and social legitimacy in Bandar Khalipah Village. In the context of the establishment of IAIN North Sumatra, his role was substantive and cultural, serving as a non-degree adjunct lecturer who taught Fiqh of Worship, strengthened Islamic values, and preserved classical Islamic scholarly traditions within the Islamic higher education environment. In addition, he also contributed as a supervisor of the Marah Halim Library of IAIN North Sumatra. This study emphasizes that the establishment of IAIN North Sumatra was supported not only by administrative and structural aspects but also by the contributions of local ulama as guardians of Islamic values and scholarly traditions.